RELEVANSI NILAI KARAKTER SISWA DALAM KITAB ADAB AL-DUNYA WA AL-DIN KARYA IMAM AL-MAWARDI DENGAN KURIKULUM BERBASIS CINTA (KBC) - Siti Zulaikhah; Imam Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the phenomenon of moral degradation among the younger generation, as well as the gap between national educational goals and educational practices that still tend to emphasize cognitive aspects over character development. On the other hand, studies on classical Islamic ethical values and modern educational approaches are still conducted separately, necessitating an integration that is more relevant to today’s educational needs. This study aims to identify character values in the book Adab al-Dunya wa al-Din by Al-Mawardi, to elaborate on the concept of the Five Loves in the Love-Based Curriculum (KBC), and to analyze the relevance between the two in the context of character education. This study employs a qualitative approach using library research. The primary data sources consist of the book Adab Al-Dunya wa Al-Din and the Love-Based Curriculum Guidelines based on the Decision of the Director General of Islamic Education No. 6077 of 2025. Data analysis was conducted using content analysis through the stages of data reduction, thematic coding, and drawing conclusions. The research results indicate that character values according to Al-Mawardiare comprehensive as they encompass intellectual, spiritual, social, and personal dimensions. These values have a strong relevance to the five pillars of Panca Cinta in the KBC, particularly regarding love for God, knowledge, fellow human beings, the environment, oneself, and the homeland. This integration demonstrates that classical Islamic educational thought can serve as a foundation for building character education that is humanistic, spiritual, and contextual for the modern generation. Keywords: Character Education, Al-Mawardi, Love-Based Curriculum